Can Free Community College Close Racial Disparities in Postsecondary Attainment? How Tulsa Achieves Affects Racially Minoritized Student Outcomes. (December 2021) - Bell, Elizabeth; Gándara, Denisa
Promise programs, or place-based tuition-free college policies, have become increasingly popular among policymakers looking to expand postsecondary attainment. In this article, we examine Tulsa Achieves, a widespread, albeit understudied type of promise program that covers the balance of students' tuition and fees after other aid is exhausted at a single community college. Utilizing a difference-in-differences and event-study design, we investigate the role Tulsa Achieves eligibility plays in promoting or hindering vertical transfer and bachelor's degree attainment across racial/ethnic groups. We find that Tulsa Achieves eligibility is associated with increases in bachelor's degree attainment within 5 years among Native American and Hispanic students and an increased likelihood of transfer within 4 years for Hispanic students.